2016
DOI: 10.1590/18069657rbcs20160006
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobial Inoculation, Alone or Coinoculated with Azospirillum brasilense, Promotes Growth of Wetland Rice

Abstract: Rhizobia and associative bacteria promote growth in rice plants (Oryza sativa L.) through a series of mechanisms, but most studies on inoculation have been performed based on inoculation with these bacteria in a separate or singular manner. The objective of this study was to assess the efficiency of single/isolated inoculation and inoculation combined with symbiotic rhizobia from forage legume and with Azospirillum brasilense on promoting growth and the root colonization process in wetland rice. Two rhizobia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
(42 reference statements)
0
6
0
4
Order By: Relevance
“…It has been demonstrated that, in wheat plants, isolates of Azospirilum obtained from this same plant species were more efficient than those isolated from plants of different species (Baldani et al, 1986). In other poaceae, such as corn (Salamone et al, 1996) and rice (Hahn et al, 2016), the effect of genotype on the interaction with bacteria has also been demonstrated.…”
Section: Resultsmentioning
confidence: 97%
“…It has been demonstrated that, in wheat plants, isolates of Azospirilum obtained from this same plant species were more efficient than those isolated from plants of different species (Baldani et al, 1986). In other poaceae, such as corn (Salamone et al, 1996) and rice (Hahn et al, 2016), the effect of genotype on the interaction with bacteria has also been demonstrated.…”
Section: Resultsmentioning
confidence: 97%
“…Puente et al [ 9 ] found that the foliar inoculation of Azospirillum brasilense Az39 increased the number and biomass of root nodules produced by Bradyrhizobium japonicum E.109 in soybean plants. This positive interaction has mainly been observed between Azospirillum and nodule-forming rhizobia [ 10 , 11 ] and has been reported to improve the response of soybean plants to drought [ 12 ] and of maize plants to salinity stress [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are important reports in the literature on the beneits of grasses grown after legumes interacting with symbiotic N-ixing bacteria [5,21,22]. Currently, among the 13 symbiotic N-ixing bacteria, including the genera Rhizobium, Mesorhizobium, Bradyrhizobium, there are the subclasses α-proteobacteria and β-proteobacteria, with two genera belonging to the Burkholderiales, and a genus Pseudomonas subclass γ-proteobacteria [23].…”
Section: Beneicial Interaction Between Grasses and Nitrogen Ixing Bacmentioning
confidence: 99%